GAMBARAN HIGIENE SANITASI INDUSTRI PANGAN RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS BAWANG I - Joko Malis Sunarno Sunarno (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2022)
There are 1208 IPRT in Banjarnegara Regency until the end of December 2020, while those who have registered and have P-IRT Certificates are 1.030.. The purpose of this study was to determine the condition of food hygiene and the place of production of the Household Food Industry (IPRT) and to determine the licensing of PIRT in the work area of Puskesmas Bawang 1. This type of research is descriptive with an observational approach. Methods of collecting data through observation and interviews using questionnaires and checklists and documentation. Data analysis used univariate analysis. The sample in the study was 20 household food industries in the work area of Puskesmas Bawang I. The characteristics of the handlers are predominantly female, 95%, aged 35-45 years, namely 45%, and having graduated from SMA/MA/SMK, namely 45%. The description of the IPRT health environment in the bad category 83%, the description of the IPRT building in the bad category 56%, the description of the roduction equipment in the bad category 76%, the description of the water supply or water supply facilities in the good category 100%, the description of the sanitation hygiene facilities and activities in the bad category 61%, The description of employee health and hygiene in the bad category of 50.8%, the description of the maintenance of the sanitation hygiene program in the bad category of 63%, the description of storage in the bad category 92%. The conclusion of the study shows that IPRT in the Puskesmas Bawang I has not shown overall good hygiene and sanitation conditions, except for the condition of water supply or water supply facilities, so public health center is expected to be able to carry out training and monitoring of IPRT in accordance with health standards.